Nutritional requirements of pheasants during the reproductive period. I. Productive parameters - Neto, Manoel Garcia; Junqueira, Otto Mack; Malheiros, Euclides Braga (Pesquisa Agropecuaria Brasileira, 1995)
This experiment with breeeder-type ringneck pheasants to study nutritional requirements was conducted on a form located at Serra Azul, SP, Brazil. One hundred and eight matrices, distributed in 18 boxes were utilized. The statistical delineation was entirely at random, with a factorial arrangement with three repetitions in which the effect of three levels of protein (18%), 20% and 22%) and two levels of methionine + cystine (7% and 9%) was studied. The results showed that the level of 22% raw protein with 7% methionine + cystine may be recommended for the diet of pheasants in the reproductive period.